Does a screening digital rectal exam provide actionable clinical utility in patients with an elevated PSA and positive MRI?. Issue 3 (4th May 2021) - Chang, Courtney M.; McIntosh, Andrew G.; Shapiro, Daniel D.; Davis, John W.; Ward, John F.; Gregg, Justin R.
Abstract: Objective: To define the value of a digital rectal exam (DRE) in the prostate‐magnetic resonance imaging (MRI) era. Prostate MRI is increasingly used in men with elevated prostate‐specific antigen (PSA) prior to biopsy. Methods: A retrospective study was performed in men with elevated PSA undergoing MRI followed by MRI fusion with systematic biopsy and men with elevated PSA/active surveillance with negative MRI followed by biopsy. Baseline clinicopathologic characteristics and DRE findings were collected. We examined performance of a positive DRE on sensitivity and specificity of diagnosing clinically significant prostate cancer (CSPC). Results: A total of 339 patients had elevated PSA and positive MRI followed by MRI fusion guided with systematic biopsy. Pre‐biopsy DRE was documented in 286/339 patients, who were included in further analysis. About 81.6% positive, 78.7% questionable, and 55.8% negative DRE patients had CSPC. Positive DRE had 21.8% sensitivity and 91.3% specificity for CSPC. Positive or questionable DRE had 42.1% sensitivity and 81.5% specificity. Among 148 men with non‐CSPC (GG1)‐targeted biopsy, 28 had systematic biopsy with CSPC. About 5/28 had positive DRE and 8/28 had positive or questionable DRE. Twenty‐seven patients were included who had elevated PSA/on active surveillance with negative MRI and biopsy done within 2 years. About 77.8% had negative, 7.4% had questionable, and 14.8% men had positive DRE. About 7.4% had CSPC and all had a negative DRE. Conclusions: Our study provides limited evidence for the value of a DRE. However, it does show occasional benefit in detecting GG2 or higher disease and given the lack of cost and side effects, should still be considered.